DAMPAK APLIKASI SELULER PADA SISTEM KOMUNIKASI BERGERAK (studi kasus mata kuliah Komunikasi Satelit pada Prodi Teknik Telekomunikasi dan Navigasi Udara) - SUKAHIR (Politeknik Penerbangan Indonesia Curug, 2012)
The basic concept of a cellular mobile communication system in particular is the division of services into small areas called cells. Each cell has a coverage area of each signal and operate in particular. The number of cells in a geographic area is based on the number of customers operating in the area. A cell is basically a radio communications center associated with MSC (Mobile Switching Central) which regulates the incoming call. Reach transmission of signals in cellular mobile communication system acceptable to good depending on the signal strength of the cell boundaries of the wearer. However, there are other factors that can be barriers to the transmitted signal can be received well. Another factor is the question of geographical factors (nature).